The message of Ecclesiastes a time to mourn and a time to dance - Kidner, Derek (Leicester, UK IVP, 1976)
Includes bibliographical references.
Copy one : "The Bible Speaks Today series has been placed in the Emmaus Bible College Library in memory of Gordon W. Craig, 1926-1990"
Keywords: Bible. O.T. Ecclesiastes -- commentaries